Bailiff Office in Albania and Changes in the Form of Organization, Under the Administrative and Implementing Reforms in Law - Puraveli, Ina; Dumi, Alba (Mediterranean Journal of Social Sciences, 2012)
This paper identifies and addresses the important factors underlying of the bailiff office in Albania and changes in the form oforganization, under the administrative and implementing reforms in law. The paper also introduces with the changes in national law,private or state organizational form. The Bailiff Section in Albania serves two key roles as part of the Judiciary. Both roles help to ensurethat justice is fairly administered and carried to its proper conclusion. The Bailiffs and their assistants serve summonses and otherimportant legal documents on parties as required by a Court or Tribunal, or as requested by a person who is a party to litigation, forexample, a court or tribunal hearing which parties are required to attend clearly cannot proceed unless there is proof that the partiesconcerned have had the summonses to attend properly served on them in a manner specified by law. The judicial power is one of theimportant part of the legal state. As stated in the Albanian constitution, one basic principle is: equality and control between governments.Our paper research will analyze the justice reforms in Albania; will analyze bailiff organizational management (private or state form).Keywords: Justice legislation , bailiff private and state services, changes in administrative services, bailiff law.